Air-exposing microwave-assisted synthesis of CuInS2/ZnS quantum dots for silicon solar cells with enhanced photovoltaic performance. Issue 124 (30th November 2015) - Hong, Ming; Xuan, Tongtong; Liu, Jiaqing; Jiang, Ziyao; Chen, Yiwei; Chen, Xiaohong; Li, Huili
Abstract : CIS/ZnS QDs were synthesized by microwave irradiation in air. The fabricated QDs/PMMA composite films were first applied to Si solar cells to improve the conversion efficiency by 3.8%. Abstract : Bright and photostable core/shell CuInS2 /ZnS QDs with emission ranging from the red to NIR were synthesized in air via a simple one-pot microwave irradiation without any inert atmosphere protection. The as-prepared CIS/ZnS QDs not only possess a high PLQY (56%) but also exhibit a large Stokes shift. They can convert near UV and blue light with lower sensitivity to the Si solar cell to red and NIR light at which the solar cell has higher sensitivity. Especially, when they were first embedded into a polymethyl methacrylate (PMMA) transparent matrix to form a composite film as a luminescent down-shifting layer for Si solar cell, the photoelectric conversion efficiency of the cell shows a marked enhancement by spectral down-shifting as compared to the bare glass substrate, and the maximum achieves 16.21%.